2018
DOI: 10.1091/mbc.e18-04-0234
|View full text |Cite
|
Sign up to set email alerts
|

ATP6AP2 functions as a V-ATPase assembly factor in the endoplasmic reticulum

Abstract: ATP6AP2 (also known as the [pro]renin receptor) is a type I transmembrane protein that can be cleaved into two fragments in the Golgi apparatus. While in Drosophila ATP6AP2 functions in the planar cell polarity (PCP) pathway, recent human genetic studies have suggested that ATP6AP2 could participate in the assembly of the V-ATPase in the endoplasmic reticulum (ER). Using a yeast model, we show here that the V-ATPase assembly factor Voa1 can functionally be replaced by Drosophila ATP6AP2. This rescue is even mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 38 publications
1
22
0
Order By: Relevance
“…Recent studies in yeast and flies suggest that ATP6AP2 contributes to the assembly of the V-ATPase proton pore in the endoplasmic reticulum (11). unknown.…”
Section: Atp6ap2 Variant Impairs Cns Development and Neuronal Survivamentioning
confidence: 99%
“…Recent studies in yeast and flies suggest that ATP6AP2 contributes to the assembly of the V-ATPase proton pore in the endoplasmic reticulum (11). unknown.…”
Section: Atp6ap2 Variant Impairs Cns Development and Neuronal Survivamentioning
confidence: 99%
“…Its role in Drosophila and Xenopus development is also established (25)(26)(27). Atp6ap2 colocalizes with V-ATPase subunits (28,29), and overexpression studies showed its coprecipitation with V 0 subunits (27) in association with V-ATPase dysfunction (30). Atp6ap2 has been proposed to chaperone V-ATPase assembly as its deletion causes reduced levels of V-ATPase subunits (18,19).…”
Section: Significancementioning
confidence: 99%
“…(3) Vma12p, Vma21p, and Vma22p correspond to transmembrane protein 199 (TMEM199), vacuolar ATPase assembly integral membrane protein (VMA21), and coiledcoil domain containing protein 115 (CCDC115), respectively, in mammals. Voa1p has been replaced by ATPase H+ Transporting Accessory Protein 1 and 2 (ATP6AP1 and ATP6AP2), (8,9) whereas Pkr1p does not have a mammalian ortholog. Whether the assembly of the mammalian V 0 is mechanistically similar to yeast V 0 assembly is currently unclear.…”
mentioning
confidence: 99%